The effectiveness of Twitter for people who suffer from depression - Ali, Susan Abubakir (2013)
A wide range of studies has investigated the role that social media plays with regard to mental health disorders such as depression: However, there are no available studies which examine the impact of using Twitter on people who suffer from depression, or any difficulties they may have faced while using it. Therefore, the aim of this research is to investigate the impact of Twitter on people who suffer from depression and to identify the challenges that they might have with Twitter also to investigate the content of the tweets. For these reasons, a questionnaire was conducted to collect data from tweeters who suffered from depression. After analysing the data, the results show that most of the participants experienced negative feelings before using Twitter, but they felt more positive after having, used Twitter, However, the major difficulties that reported by them were related to finding useful tweets about depression, finding tweeters who support them, making self-disclosing in such a public platform. Furthermore, 13,279 public tweets that mentioned depression were retrieved using Twitter API 1.1. Consequently, these tweets have been analysed using a mixed methods approach. Firstly, the content analysis was used, which revealed that the negative emotions, "sad" and "anxious" were the most common emotions mentioned in the depression tweets compared to random tweets. Strongly suggesting that tweeters aim from the tweets was to make self-disclosing about depression. However, the anger emotion and "I" was mentioned less in their tweets. Therefore, Twitter might not be easy enough to be used by depressed tweeters who are angry. In addition, the "public" feature might prevent them from using "I" in their tweets. Consequently, an inductive thematic analysis revealed three major themes: disseminate information or link of information, self-disclosing and overall opinion. The results of this research identified the requirements for designing a new application for Twitter that can better support people with depression and improve their experience with Twitter.